Seismic Retrofitting of Existing Steel Frames with External BRBs: Pseudo‐Dynamic Hybrid Testing and Numerical Parametric Analysis - Freddi, Fabio; Wu, Jing‐Ren; Cicia, Massimo; Di Sarno, Luigi; D'Aniello, Mario; Gutiérrez‐Urzúa, Fernando; Landolfo, Raffaele; Kwon, Oh‐Sung; Bousias, Stathis; Park, Jamin; Stathas, Nikolaos; Strepelias, Elias (Earthquake engineering & structural dynamics, 2025)
ABSTRACT The use of buckling‐restrained braces (BRBs) is an effective strategy for improving the seismic performance of existing structures. BRBs can be included within existing frames, creating an additional load path and contributing to their strength, stiffness, ductility, and, in turn, energy dissipation capacity. However, BRBs are typically inserted within the structural mesh of the existing frames, thus requiring the demolition and reconstruction of non‐structural components. The present study explores the seismic retrofitting of existing steel structures, considering an external placement of BRBs to minimize the invasiveness of the intervention scheme and, consequently, business interruptions and indirect losses. A two‐story steel moment‐resisting frame (MRF) designed primarily for gravity loads and retrofitted with BRBs placed externally to the frames were considered for case study purposes. The research includes large‐scale Pseudo‐Dynamic Hybrid tests performed as part of the HITFRAMES (i.e., HybrId Testing of an Existing Steel Frame with Infills under Multiple EarthquakeS) project funded by the EU‐H2020 SERA Consortium in Europe. The experimental results provided significant insights into the seismic response of the retrofitted structure and allowed the calibration of advanced 3D finite element models. An extensive numerical parametric analysis was performed to investigate some of the key variables affecting the local and global response of the structure. The results provide valuable insights into effectively implementing this retrofit solution and the influence of BRB eccentricity on the seismic response.